Written discourse in digital audio folklore - Mansor, Noraien; Rahim, Normaliza Abd (Serials Publications, 2017)
This study focuses on analysing the written discourse of two song lyrics. The song lyrics were taken form the ‘Kingfisher Series’ song album copyright by Dewan Bahasa dan Pustaka. The song lyrics were chosen due to the same adjectives and moral values in the story. The song lyrics were analyzed by using the critical discourse analysis where each stories were analysed according to song lyrics and also the storylines. The results of the study revealed that the story ‘The Stingy Man’ showed that the character ignored the poor and family and instead would prefer his money. The story ‘The Metal Fishing Rod’ showed that one of the best friends were stingy by choosing the golden rod and ignore the metal rod. This also showed that although they are best of friends, the friend will still ignore their other friend for the sake of wealth. It is hoped that other studies will help readers and listeners in the better understanding of folklores.